Pengaruh kualitas produk dan kualitas pelayanan terhadap kepuasan konsumen pada PT. Ogos indonesia gemilang di Pekalongan - Dyahtritami, Vigi Reinaning; Utami, Fitriani Nur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Quality is the main key to products being recognized and trusted by the wider community. Quality products have an important role in building customer satisfaction. The better the quality of the product provided, the higher the level of customer satisfaction. This also applies to service quality. If the quality of service provided to consumers is good, it will result in a sense of satisfaction from consumers for the company. The study aims to determine the effect of product quality and service quality on customer satisfaction at PT Ogos Indonesia Gemilang in Pekalongan. The type of research that will be used by the author in this study is quantitative with descriptive causal (cause-and-effect) methods; the aim is to determine whether or not there is an influence or relationship between the independent variable and the dependent variable. The sampling technique used in this study is purposive non-probability sampling. The results showed that product quality and service quality had a simultaneous and partial effect on customer satisfaction at PT Ogos Indonesia Gemilang in Pekalongan.